Pertimbangan Kebutuhan Bisnis Dan Kesiapan Organisasi Untuk Berubah Sebagai Dasar Pengambilan Keputusan Re-Engineering Sebagai Strategi Peningkatan Mutu = Considering Business Needs And Organizational Readiness For ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Background: Strategies for improving quality can be formulated based on analyzing the busi¬ness needs and the organizational readiness to change. Based on this analysis, four strategies can be developed, they are: survival, launch reengineering, reconsider, and advantage. Instru¬ments to evaluate the business needs and the organizational readiness to change, are there¬fore needed in order to help the organization to choose possible strategies for improving quality. Method: Instruments for evaluating business needs and organizational readiness were deve¬loped by training facilitators at Bapelkes Gombong, tested among 50 respondents, checked for reliability and validity, reviewed by the administrators consisted head of the center, secretary, heads of section, and head of quality committee, and re-tested among 20 respondents. Result: The revised instruments showed the Cronbach Alpha 0.7224 for business needs, and 0.9272 for organizational readiness, and the instruments showed the expected strategy for improving quality of services at Bapelkes. The instruments had some limitations considering the cross-sectional approach being used, and the limitations of factors under study. Conclusions: The instruments for evaluating business needs, and organizational readiness to change as a basis for developing quality strategy can be used as a rapid assessment tool, that should be followed by in depth analysis considering the limitations of the instruments.